OBSERVATIONS ON THE FECUNDITY, LARVAL DEVELOPMENT AND EARLY GROWTH OF LABEQ BATA (HAMILTON) - Alikunhi, K H (Indian Journal of Fisheries, 2015)
Labeo bata is a medium-sized Indian carp, attaining a maximum length of 20-24 inches. It has a fairly wide distribution, occurring throughout upper India and extending south up to the Krishna River System. Considered a tasty food fish, it is generally kept in ponds along with the major carpsi but its growth is comparatively slow. Nothing is known about the life history of this species except for certain post-larval stages very briefly described by Mookerjee et al. (1944). Elucidation of the complete life-history of this species will enable identification of its various stages from those of the major carps. Like the major Indian carps L. bata does not breed in ordinary ponds, although it breeds in rivers during the monsoon months.